#CleftProud: A Content Analysis and Online Survey of 2 Cleft Lip and Palate Facebook Groups. (November 2018) - Stock, Nicola Marie; Martindale, Anna; Cunniffe, Claire
Background: More than 2 billion people worldwide now use social networking sites, with an increasing number of users accessing these sites to obtain health information and engage in emotional support. Yet, investigation of social networking sites in the context of cleft lip and/or palate (CL/P) has been scarce. Methods: Real-time data posted during 2 weeks in April 2017 were collected from 2 existing private Facebook groups (hosted by the Cleft Lip and Palate Association United Kingdom) using video screen capture software. The number of posts, comments, unique contributors, and post "likes" was recorded, as well as the type and theme of each post. Data relating to the benefits and challenges of participation in the 2 groups were also collected via an online survey. Results: A content analysis of real-time data identified perioperative care, associated syndromes, and dental health to be particular areas of concern for parents/caregivers. Expectations, experiences, and outcomes of further treatment were key topics of discussion for adults with CL/P. Common benefits of the groups included the ability to connect with others, learn about local events, give and receive emotional support, and obtain quick responses to queries in a semi-anonymous environment. Disadvantages of the groups included a reliance upon opinion rather than medical fact and the frequent use of inappropriate terminology. Conclusions: Social networking sites appear to be a helpful source of health-related information and peer support for the CL/P population, yet closer monitoring of these groups may be required.